Total hip arthroplasty without femoral osteotomy in patients who had high and low dislocation due to developmental dysplasia of the hip - BEZER, MURAT; TOPKAR, OSMAN MERT (SAGE PUBLICATIONS LTD, 2016)
Background: Various surgical techniques and outcome results have been reported after primary total hip arthroplasty for the treatment of patients dysplastic hips. Low failure and complication rates have been reported when the acetabular component has been placed in the true acetabulum. The current study reports the results of primary total hip arthroplasty in patients with high and low dislocation for whom the acetabular component was placed in the true acetabulum without femoral or trochanteric osteotomy. Methods: 26 primary total hip replacements were performed on 22 patients. The mean duration of follow-up was 8.9 years. There were 4 men and 18 women. 17 hips were classified as type B (low dislocation) and 9 as type C (high dislocation), according to the classification system of Hartofilakidis et al. Acetabular components were placed in the true acetabulum without osteotomy for all patients. Results: At the time of final follow-up (mean 8.9 years) the average Harris Hip Score was 85 points. Femoral head autograft was used in 9 hips to supplement acetabular coverage. In 8 patient linear calcar fracture. 7 fixed with Dall-Mile cable and 1 fixed with a side plate. On radiologic evaluation, 2 incidents of asymptomatic osteolysis, 1 of acetabular loosening, 1 graft resorption, and 1 impingement (correlated with physical examination) were identified. 2 patients had neuropraxia and were treated medically. There were no early or late infections. Only 1 patient with acetabular loosening required revision surgery. Conclusions: Although it is surgically difficult to place the acetabular component in the true acetabulum without femoral or trochanteric osteotomy, at the final follow-up we report favourable results. Long-term follow-up is needed to verify our results.
Keywords: Arthroplasty; Dislocation; Dysplasia; Hip; SUBTROCHANTERIC SHORTENING OSTEOTOMY; CROWE TYPE-III; TOTAL REPLACEMENT; BONE-GRAFTS; FOLLOW-UP